Determinan Harga Saham Subsektor Makanan Dan Minuman: Peran Debt To Equity Ratio, Return On Equity, Dan Dividend Payout Ratio - Heri Sastra; Cindy Fransisca (Jurnal Aplikasi Bisnis Kesatuan, 2025)
This study examines the effects of Debt to Equity Ratio (DER), Return on Equity (ROE), and Dividend Payout Ratio (DPR) on stock prices among food and beverage companies listed on the Indonesia Stock Exchange. The issue is important because stock price reflects market valuation and serves as a key signal for investors in assessing investment prospects and risks. The study applies a quantitative approach using secondary data from financial statements and closing stock prices of 10 companies during 2017–2021, resulting in 50 firm-year observations. The data are analyzed using multiple linear regression after classical assumption tests. The findings indicate that DER, ROE, and DPR jointly have a significant effect on stock prices. Partially, ROE has a positive and significant effect, whereas DER and DPR have positive but insignificant effects. The adjusted R square of 38.2% indicates that the three financial variables explain a meaningful proportion of stock price variation, while the remaining variation is attributable to other factors beyond the model. The study highlights that equity-based profitability is the strongest fundamental signal for investors in the food and beverage subsector, while leverage and dividend policy are not yet dominant determinants of stock prices. Keywords: Debt to Equity Ratio, Return on Equity, Dividend Payout Ratio, stock price, food and beverage.